Industrial relations in the EU and other global economies 2006-2007 (Dublin, 2008)
"This annual review highlights the most significant industrial relations developments in the EU, Japan and the US in 2006–2007. In particular, it focuses on working time developments and the challenges of globalisation in these economies. The first part of the review sets the scene by examining the main industrial relations which have already taken place – more specifically, economic, legislative and social partner developments. The second part of the review presents an overview of working time regulation and management in the EU, Japan and the US. The study reviews the most recent trends in working time, covering usual weekly working hours, overtime and long working hours, flexible work schedules, shift work and weekend work. Furthermore, it looks at provisions for maternity and parental leave in the three economies under examination. While the study essentially covers the EU Member States, Japan and the US, it also includes references to emerging economies such as Brazil and China."